The Israeli product boycott movement in the perspective of consumer protection law in Indonesia - Setyawati, Ria; Aryatie, Indira Retno; Abdul Rahman, Nasarudin (Sabat Ilmu Aditya, 2025)
The boycott of Israeli products in Indonesia reflects both solidarity with Palestine and the exercise of consumer rights. This study aims to analyze the boycott movement from the perspective of Indonesian consumer protection law, particularly Law No. 8 of 1999 on Consumer Protection (UUPK). Using a normative juridical method with a statute and conceptual approach, the research examines how consumer rights are exercised in ethical consumption practices and how legal obligations are imposed on businesses. The findings indicate that boycotts can be regarded as part of consumers’ rights to make choices based on moral and ethical considerations, although legal and economic challenges may arise. Businesses are required to provide accurate product information, while unclear labeling often hinders consumer decision-making. The study also discusses the legal and economic implications of boycotts in the context of international trade, underscoring the importance of regulatory frameworks that ensure transparency and strengthen consumer protection when ethical dilemmas shape purchasing decisions